(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
A positive psychological climate of a high level can serve as a powerful tool for the harmonious formation of a person’s personality under the influence of others (group, community). Psychological climate is realized under two main factors: the socio-psychological state of society and microsocial conditions. The socio-psychological state (conditions) of society is expressed in the conditions of treatment, values, and opportunities established by law, while microsocial conditions are expressed in the legal status, division of labor, environmental conditions, age or gender of a group or community, and the formation of mutual relations.